The Distribution and Abundance of Black Band Disease and White Syndrome in Kepulauan Seribu, Indonesia - Ofri Johan; Dietriech Geoffrey Bengen; Neviaty Putri Zamani; . Suharsono; Michael John Sweet (Bogor Agricultural University, Indonesia, 2015)
Coral diseases that have emerged since the early 1970s have caused significant regional ecological impacts. However, there has been a paucity of research into coral disease in South-East Asia, including Indonesia. This study provides baseline coral disease data in the Kepulauan Seribu Marine National Park. In this study we show a positive correlation between overall coral cover and the dominant reef building coral Montipora spp. and found two main diseases, black band disease (BBD) and WS, were highly prevalent throughout all reefs. Based on spatial location, the highest abundance of BBD (0.08 col./m2) was found at sites nearer (zone 1) to the mainland, whilst for WS (0.05 col./m2) highest abundance was found at middle sites (zone 2). According to the temporal data, the highest abundance of BBD (0.77 col./m2) was found during the transition period (between wet and dry seasons), whereas for WS higher abundance occurred within the dry season (0.07 col./m2). There was a significant difference in disease abundance among seasons which was correlated with increasing temperature and light intensity along with variations in total organic matters, nitrite and phosphate levels. Moreover, the middle sites experienced additional stress from the waste material originating from the mainland.